"The Evaluatıon Of Results In Class Iı, Dıvısıon 1 Malocclusıons Treated By Bıonator" - Mehmet Demir Yiğit; Serdar Z. Akın (Galenos Yayinevi, 1989)
In this study was purposed to evaluate treatment results of the Class II, Division 1 cases whom were treated with the Balters's Bionator. The investigation was performed on ten patients who have Class II, Division 1 malocclusion. On the other hand, another group consisting of ten individuals who have Class II, Division 1 malocclusion and who haven't been treated before, has been selected control group. Treatment groups before and after the treatment and the control group at the beginning and at the end of the two years period having been taken lateral cephalometric films, statistical evaluation of the data which consist of angular and dimensional measurements has been realised. According to investigation, the changes of mandible and maxilla on Bionator's treatment group were take placed both the dentoalveolar and skeletal level.